Identification of Arboreal Vegetation and Potential Areas in the Commercial Center of Capitão Poço, Brazil - Silva, Washington Duarte Silva da; Pereira, Jordan Luis Campos Modesto; Costa, Milton Garcia; Santos, Adriane dos Santos; Farias, Magda do Nascimento; Ferreira, Ana Paula Souza; Abreu, Luiz Carlos Pantoja Chuva de Abreu; Silva, Lucila Ferreira da; Siqueira, Maria Thalia Lacerda (Journal of Agricultural Studies, 2021)
Green spaces are urban spaces that bring man and nature closer together, positively influencing the quality of life of the population. The planning of green spaces is essential in urban areas and Geographic Information Systems (GIS’s) are tools capable of assisting in the identification, management and monitoring of these spaces. The objective of the work was to map the urban vegetation and carry out a survey of potential areas for parks and green areas in the commercial center from the municipality of Capitão Poço - PA. The study was carried out in the commercial center from Capitão Poço, PA - Brazil by obtaining images from the Google Earth software and photointerpreted with the aid of the QGIS software. Finally, the current and potential tree green areas were identified in the georeferenced images. The survey of green areas in the commercial center identified that only 4.74% of the total area contains tree vegetation, in addition to 53% of this vegetation being found around the mother church and the municipal square of Alvorada. For potential green areas, it was found that the commercial center has 5,873.5% more potential areas in relation to current tree vegetation. In this sense, it is observed that the commercial center from the municipality of Capitão Poço contains a low proportion of areas with arboreal vegetation and a high potential for the implantation of parks, forests and other types of green areas.